Pathophysiology of Dengue haemorrhagic fever: an autopsy cases series during an outbreak in 2019, Galle, Sri Lanka - H. Dandeniya-Arachchi; R. Ruwanpura; S. Hulathduwa (Infectious Diseases and Tropical Medicine, 2021)
OBJECTIVE: Dengue is a mosquito-borne Arbor-viral infection with four main subtypes. Sri Lanka has been affected by several dengue epidemics during the last three decades. The clinicopathological entities of dengue may differ with each individual subtype or combination. This study describes clinicopathological findings of a series of 7 fatal dengue cases during an outbreak in early 2019, mainly due to Dengue virus three serotype (DENV3).